Electrodeposition of Pr-Mg-Co ternary alloy films from the choline chloride-Urea ionic liquids and their corrosion properties. Issue 6 (4th May 2020) - Li, Miao; Chen, Bi Qing; Xiong, Tong Tong; Gao, Li Xia; Du, Chan; Zhu, Yun Na; Zhang, Shi Ming
Abstract: This paper aims to obtain rare earth magnesium alloy with good adhesion and corrosion resistance. The work was concerned with the electrochemical behaviors of Co(II), Mg(II), Pr(III) on Pt and Cu electrodes in choline chloride-urea ionic liquids by electrochemical techniques of cyclic voltammetry. The electrodeposition conditions of Pr-Mg-Co ternary alloy films on copper substrate from the choline chloride-urea ionic liquids with different metal salts were investigated by potentiostatic electrolysis. The author has used scanning electron microscopy coupled with energy dispersive X-ray spectroscopy to study the surface morphology and composition of Pr-Mg-Co ternary alloy film, Polarization curves are tested. Results shows under −1.15 V voltage, the alloy films with evening is obtained when the concentration ratio of Pr(III)/Mg(II) is 4:3, and deposition time is 30 min .it showed that the content of Pr in the alloy film has reached up to 13.22 wt.%, and the morphology of black alloy coating is amorphous and has micro-cracks, which reflects the alloy films has good corrosion performance in alkaline solution. This can be attributed to its dense film structure and good adherence to the substrate. It provides some technology for the production of corrosion- resistant materials. Graphical Abstract: